Pengaruh Cita Rasa dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Dengan Kepuasan Pelanggan Sebagai Variabel Intervening: Studi Pada Pelanggan Dapoer Mbok Sum Kediri - Andhini Fitria Nurmalasari; Taufik Akbar; Zulfia Rahmawati (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study investigates the impact of taste and service quality on customer loyalty, with customer satisfaction serving as a mediating variable, at Dapoer MbokSum Kediri. The research adopts a quantitative approach, utilizing both primary and secondary data sources. Primary data were obtained through the distribution of structured questionnaires to customers, while secondary data were collected via interviews with the business owner and direct field observations to gain a deeper understanding of operational practices. A total of 120 respondents were selected through accidental sampling, ensuring that participants met specific criteria relevant to the study objectives. The data analysis was conducted using SmartPLS 4.0, incorporating validity and reliability testing to ensure the robustness of the measurement instruments, as well as hypothesis testing to evaluate the relationships between variables. The results of the analysis indicate that both taste and service quality exert significant and positive influences on customer satisfaction. Furthermore, service quality demonstrates a significant and direct positive effect on customer loyalty. In contrast, taste does not show a direct influence on loyalty, suggesting that its effect on loyalty is more indirect and mediated by satisfaction Additionally, the mediation analysis confirms that customer satisfaction plays a critical role in linking both taste and service quality to customer loyalty. This implies that while customers may appreciate the taste of food, it is their overall satisfaction—encompassing both taste and service experiences—that ultimately drives loyalty. The study highlights the importance for culinary businesses, particularly in the competitive food service industry, to focus not only on product quality but also on delivering excellent service to enhance satisfaction and foster long-term customer relationships. The findings provide practical insights for Dapoer MbokSum Kediri and similar establishments to strategically prioritize service quality improvements alongside maintaining food taste to maximize customer retention and loyalty.